Finding a Mathematical Model for Predicating Trip Generation from and to Tishreen University - اسعد شذى; زنتوت سارة (Latakia University Journal -Engineering Sciences Series, 2021)
Tishreen University suffers from transportation problems to and from it in the absence of accurate and comprehensive planning for the movement of transportation in the city or for the movement of transportation to the university in particular in addition to the growing population growth in the city and the lack of transportation services with the required quality. This research provides a study of the trip generation to and from Tishreen University from various zones in Lattakia and a study of the impact of economic and social characteristics on the formation of transportation. This study was conducted on Tishreen University , which constitutes the main transportation attraction in the city of Lattakia , as abasis for studying transport planning in the city through which special policies will be developed to evaluate current and future transport networks to accommodate traffic volumes and the lack of bottlenecks and congestions on any part of the network and setting alternatives and choosing the best ones, with the possibility of generalizing this study to universities in the rest of the Syrian governorates